Blood pressure around the menopause: a population study - Cifkova, Renata; Pitha, Jan; Lejskova, Magdalena; Lanska, Vera; Zecova, Silvia (Journal of hypertension, 2008)
BACKGROUND: Hypertension is a major cardiovascular risk factor possibly explaining the excessive cardiovascular morbidity and mortality in postmenopausal women. Cross-sectional and longitudinal studies have explored this issue with diverging results. Our study sought to elucidate the impact of the menopause on blood pressure in a representative population sample. METHODS: The study involved randomly selected 908 female residents of a Prague district, aged 45-54 years (respondence rate, 63.9%). Three definitions of the menopause were used: self-reported menstrual characteristics (premenopausal with the final menstrual period less than 60 days; late menopausal transition, with final menstrual period 60-365 days; and postmenopausal, final menstrual period more than 365 days before the examination), levels of follicle-stimulating hormone (< or = 40 IU/l for premenopausal and more than 40 IU/l for postmenopausal women), and both. RESULTS: Age-adjusted and BMI-adjusted systolic blood pressure and diastolic blood pressure did not differ among the groups regardless of the definition of menopause. There was also no difference in the prevalence of hypertension and in the age-adjusted and BMI-adjusted odds ratio for hypertension. Multiple regression analysis testing the association between systolic blood pressure and diastolic blood pressure, and age, BMI, heart rate, smoking, and antihypertensive medication explained a rather small proportion of the BP variation. No correlation was found between BP and age in either subgroup; the closest correlation was always found between BP and BMI. CONCLUSION: In our rather homogeneous representative population random sample of women around the menopause, the rise in blood pressure after the menopause appeared to be due to increased BMI rather than to ovarian failure per se.
Keywords: Weight Gain; Cross-Sectional Studies; Female; Humans; ženské pohlaví; Perimenopause; krevní tlak; lidé; index tělesné hmotnosti; lidé středního věku; hypertenze; průřezové studie; perimenopauza; Blood Pressure; Body Mass Index; Hypertension; hmotnostní přírůstek; Middle Aged